A model to think about crypto-assets and central bank digital currency - Hernán D. Seoane (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
This paper introduces digital assets, crypto assets in general, and Central Bank Digital Currency in particular, into an otherwise standard New-Keynesian closed economy model with Financial Frictions. We use this setting to study the impact of a change in preferences towards the use of digital assets and to address whether the emergence of this type of instruments affect the transmission of monetary policy shocks. In this context we study the introduction of Central Bank Digital Currencies. The model is stylized but it could be a baseline for the design of models for quantitative analysis.
Keywords: E00; E4; E5; 330; New Keynesian; Crypto assets; Central Bank Digital Currency